(untitled) (Journal of Numerical Optimization and Technology Management, 2024)
The study aimed to compare the patient’s attendance to Klinik Rawatan Keluarga Pergigian (KRKG), Hospital Universiti Sains Malaysia (Hospital USM) from the year 2017 to the year 2020. Data was collected starting from January 2017 till December 2020. Data was plot according to the trendline for each year, and the mean of patient’s attendance is being calculated, recorded, and present using a simple bar means. The equation for the particular year is being estimated and compared to the reference category using multinomial regression. From the analysis, it was found that the year 2020 having a decreasing [F-Stat (df)=6.786(1.759,19.349); p < 0.05] in the trendline of patients who attended KRKG, this is due to the global coronavirus pandemic. The finding had found that the year 2020 having has a significant decrease as compared to the previous year [F-Stat (df)=6.786(1.759,19); p < 0.05]. In the multinomial regression analysis, the estimates for the parameter can be identified compared to a baseline category. The finding had shown that the patient’s attendance to KRKG is less due to the Covid-19 pandemic.